Necrotizing Pneumonia Caused by Panton-Valentine Leucocidin-Producing Staphylococcus aureus Originating from a Bartholin's Abscess - N. Jung; C. Lehmann; M. Hellmann; H. Seifert; M. M. Valter; M. Hallek; G. Fätkenheuer; M. Kochanek (Hindawi Limited, 2008)
Background. Panton-Valentine leukocidin (PVL-)producing Staphylococcus aureus is emerging as a serious problem worldwide. There has been an increase in the incidence of necrotizing lung infections in otherwise healthy young people with a very high mortality associated with these strains. Sporadic severe infectious complications after incision of Bartholin's abcesses have been described but involvement of S. aureus is rare. Case report. We present a 23-year-old apparently healthy female patient without any typical predisposing findings who developed severe sepsis with necrotizing pneumonia and multiple abscesses following incision of a Bartholin's abscess. Methicillin-sensitive S. aureus harbouring Panton-Valentine leucocidin genes were cultured from the abscess fluid, multiple blood cultures and a postoperative wound swab. Aggressive antibiotic therapy with flucloxacillin, rifampicin and clindamycin, drainage and intensive supportive care lead finally to recovery. Conclusions. S. aureus, in particular PVL-positive strains, should be considered when a young, immunocompetent person develops a fulminant necrotizing pneumonia. Minor infections-such as Bartholin's abscess-can precede this life-threating syndrome. Bactericidal antistaphylococcal antibiotics are recommended for treatment, and surgical procedures may become necessary.